Identificação de marcadores moleculares de transformação maligna dos neurofibromas plexiformes em pacientes com neurofibromatose tipo 1 - Cinthia Vila Nova Santana (2018)
Introduction: The main characteristics of Neurofibromatosis type 1 (NF1) are café-au-lait spots (CAL), axillary or inguinal freckling and neurofibromas. Plexiform neurofibromas (PNFs) are initially benign tumors, which can transform into malignant peripheral nerve sheath tumors (MPNSTs). Currently, there are no specific molecular markers that can predict the malignant process of the plexiform tumor. Objective: To identify molecular markers that help in the early identification of MPNST. Methods: MLPA (n = 48 NF1), relative telomere length (n = 49 controls, n = 49 NF1), genotyping of TERT (rs10069690, rs2853660 and rs2736100) (n = 79 controls, n = 95 NF1), TNF-α (rs1800669) (n = 58 NF1) and AKT1 (rs1130214 and rs3803304) (n = 58 NF1) polymorphisms. Systematic review and in silico analysis of microRNAs described in the literature for NF1 were also performed. Results: The MLPA detected deletions in 14.58% of the patients. NF1 subjects showed longer telomeres than controls, but no difference was seen between NF1 subgroups (asymptomatic PNF, symptomatic PNF and MPNST). Only rs10069690 (TERT) presented a significant association with malignancy of the plexiform tumor (OR = 10.33 for the presence of allele T). 75 microRNAs were identified, of which eight were more frequent (miR-210, miR-10b, miR-130b, miR-137, miR-214, miR-146a, miR-150, miR-195). The main biological pathways involved in the pathogenesis of NF1 identified were: cell-cell signaling, cell differentiation, transmembrane transport, lipid metabolism, transcription regulation and post-transcription, posttranslational protein modification, histone modification, MAPK pathway activation, apoptosis and regulation of neurogenesis, angiogenesis, and growth. Conclusion: MLPA and relative telomere length did not show sufficient evidence to differentiate the stages of the plexiform tumor in NF1, whereas the polymorphism rs10069690 seems to contribute in this process. MicroRNAs, although quite heterogeneous, present a potential as biomarkers in this disease.